Chronic treatment with tetrahydrobiopterin reverses endothelial dysfunction and oxidative stress in hypercholesterolaemia. - Cosentino, F; Hürlimann, D; Delli Gatti, C; Chenevard, R; Blau, N; Alp, N; Channon, K; Eto, M; Lerch, P; Enseleit, F; Ruschitzka, F; Volpe, M; et al. (2008)
BACKGROUND: Reduced availability of tetrahydrobiopterin (BH(4)), an essential cofactor of nitric oxide (NO) synthase (NOS), decreases NO production and increases reactive oxygen species. Both mechanisms contribute to atherosclerotic vascular disease. Although acute supplementation of BH(4) improves endothelial dysfunction, the effect of chronic BH(4) in humans is unknown. OBJECTIVE: To investigate the effect of chronic BH(4) supplementation on endothelial function and oxidative stress in hypercholesterolaemia. DESIGN: Randomised double-blind, placebo-controlled trial. SETTING: University Hospital. PATIENTS: 22 hypercholesterolaemic patients (low-density lipoprotein (LDL) >4.5 mmol/l) were randomised to 4 weeks of oral BH(4) (400 mg twice daily) or placebo. Age-matched healthy volunteers served as controls. MAIN OUTCOME MEASURES: Endothelium-dependent and -independent vasodilatation was assessed by venous occlusion plethysmography. To elucidate the mechanisms of BH(4) effect, NO release and superoxide anion (O(2)(-)) production were measured in human aortic endothelial cells exposed to native LDL (2.6 mmol cholesterol/l). RESULTS: BH(4) plasma levels were significantly increased by oral supplementation. NO-mediated vasodilatation to acetylcholine was reduced in patients compared with controls and restored by BH(4). No effect of BH(4) on endothelium-independent vasodilatation was seen. Furthermore, 8-F(2 )isoprostane plasma levels, a marker of vascular oxidative stress, were reduced by BH(4). In LDL-treated endothelial cells, BH(4) levels and NO release were reduced and O(2)(-) production increased compared with control cells. Exogenous BH(4) normalised NO and O(2)(-) production. CONCLUSIONS: In hypercholesterolaemia, endothelial dysfunction and oxidative stress can be reversed by chronic oral treatment with BH(4). Thus, BH(4) availability is essential for maintaining NO synthesis and low O(2)(-) production by endothelial NOS in vivo, and may provide a rational therapeutic approach to prevent cardiovascular disease.